TERMS REPRESENTING HYDRAULIC ENGINEERING STRUCTURES AND THEIR LEXICAL-SEMANTIC CLASSIFICATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This work is dedicated to the scientific analysis of the linguistic features of terms representing hydraulic engineering structures. It examines the etymology, structural composition, and semantic groupings of these terms, highlighting their usage in key areas such as water management, irrigation, drainage, water supply,dams, and canals. The study also analyzes the alignment of these terms with international terminology and their role within national terminological practice. The results contribute to the standardization of hydraulic engineering terminology, facilitate the work of specialists and translators in the field, and improve the quality of scientific and technical literature.